Subsection Evolution in GA for Trajectory Planning of a Space Manipulator. (9th May 2013) - Zeng, Cen; Wei, Xiaopeng; Zhang, Qiang
Abstract A free-floating space manipulator has outstanding advantages and wide application prospects compared with other categories. This paper discusses the concepts and categories of space robots and introduces the current trajectory-planning algorithm for a space robot and its ground simulation system in the main countries of the world. This paper also constructs a system model for the space manipulator system and gives the kinematic equation of such a manipulator system. A dynamic equation of the manipulator's joints is also developed by using Lagrange equations. Continuous Cartesian trajectory planning is also studied in this paper based on differential kinematical equations and momentum conservation equations. Finally, this paper presents the subsection evolution algorithm in GA to realize the trajectory tracking of a free-floating space manipulator and a simulation about the free floating space manipulator and its corresponding analyses are given.